Argumentation in the initial training of science teachers about the socio-scientific issue xenotransplantation - Idalino, Rosane Karine Tavares (2023)
This study presents an excerpt from a master's degree research and aims to identify the argumentative skills of science undergraduates regarding the socio-scientific issue xenotransplantation. Socio-scientific issues (SSI), due to their controversial character and because they encompass social issues, are identified as potentially good for generating arguments. Xenotransplantation is one of these SSI that can be addressed in science classes, and it corresponds to the transplantation of organs or tissues from non-human animals to human beings. Methodologically, the present work has a qualitative nature. The target audience of the research were science teachers in initial training at the Federal University of Sergipe, University Campus Professor Alberto Carvalho, located in the city of Itabaiana, Sergipe State. Data collection was made by means of focus groups and the analyzes were carried out according to argumentative pattern proposed by Toulmin (2006). The results showed that science undergraduates were able to elaborate arguments, however, according to what Toulmin's argumentative pattern assumes, most of these arguments presented a simple structure, with few elements. Regarding xenotransplantation as a socio-scientific issue, it proved to be an efficient promoter of discussion.